Pemberdayaan Masyarakat Berupa Skrining Lansia Berbasis Web bagi Tenaga Kesehatan dan Kader Lansia - Hartaty Sarma Sangkot; Avid Wijaya (Ilin Institute, 2021)
The aim of this community service was to develop collaboration with Puskesmas Bareng, Malang City, in order Puskesmas still could perform service for elderly people in this new normal era supported by Management Information System (MIS) Elderly. Methods used in this community service was need assessment, tutorial, practice and accompaniment of kaders and health officers in using this MIS elderly. The result was application called as MIS elderly which was developed based on need assessment in Puskesmas Bareng and socialization of MIS elderly to health officer in Puskesmas Bareng, Malang City. At the end of community service, there was evaluation using model Technology Acceptance Model (TAM). The model was consisting of 4 parts, which are Perceived Ease of Use (PEOU, Perceived Usefulness (PU), Behavioural Intention (BI) and Actual Usage (AU). As the summary, all the health officers agree that this application is easy to used, very helpful, motivate the users to keep using the application and very needed to support Puskesmas Bareng in provide service for elderly in their Puskesmas.